The Angola Low: relationship with southern African rainfall and ENSO. - (:unkn) unknown (My University, 2019)
The main states of the Angola Low (AL) are identified using clustering analysis applied to daily anomalous patterns of 700-hPa wind vorticity over Angola and adjacent countries from November to March for the 1980/81–2014/15 period. At the daily timescale, we examine the extent to which the main states of the AL modulate daily rainfall over southern Africa. At the interannual timescale, we assess both the relationship between the occurrence of these AL states and El Niño southern oscillation (ENSO) and the role of the AL in explaining ENSO’s failure in driving southern African rainfall at times. Three reanalyses are considered to account for uncertainties induced by the scarcity of data available for assimilation over southern Africa. Three preferential states of the Angola Low are identified: AL state close to its seasonal climatology with slight zonal displacements, anomalously weak AL state and anomalously strong AL state with meridional displacements. These different states all significantly modulate daily southern African rainfall. Near-climatological AL state promotes wet rainfall anomalies over eastern subtropical southern Africa and dry rainfall anomalies over its western part. A slight westward shift in the near-climatological position of the AL leads to reversed zonal gradient in rainfall. The remaining regimes significantly modulate the meridional gradient in southern African rainfall. Anomalously weak and anomalously northward AL states promote wet rainfall anomalies over tropical southern Africa and dry rainfall anomalies over subtropical southern Africa. The reverse prevails for anomalously southward AL. At the interannual timescale, ENSO significantly modulates the seasonal occurrence of most AL states in the three reanalyses. Anomalously weak and southward AL states are more strongly correlated with regional rainfall than ENSO in all reanalyses, suggesting that accounting for AL variability may improve seasonal forecasts. Case study
Keywords: African Research